Is there a difference between normotensive and hypertensive patients in terms of blood parameters and cardiovascular diseases? - Aydın, Cihan; Alpsoy, Şeref; Engin, Mesut; Yavuz, Senol (The European Research Journal, 2021)
Objectives: It has been stated in various studies that there is a difference in some blood parameters between hypertensive and normotensive patients for a long time. Mean platelet volume (MPV), and red blood cell distribution width (RDW), have been studied in hypertensive patient groups in many studies. Hypertension is a classic risk factor for ischemic stroke and myocardial ischemia, as known. In our study, we examined whether there was a difference between hypertensive patient groups and normotensive patients in terms of blood parameters such as MPV and RDW, and the incidence of stroke and myocardial infarction. Methods: Blood samples and twenty-four-hour ambulatory blood pressure monitoring (ABPM) results of 552 patients admitted to our outpatient clinic with a pre-diagnosis of hypertension were retrospectively analyzed. According to ABPM results, we divided the study participants into four groups; dippers, non-dippers, extreme dippers, and normotansives. Complete blood count and biochemical test results were found in the database of our hospital for all patients and differences between groups were investigated. Results: One hundred seventy three normotensives (Group 1) (mean age, 47.4 ± 15.4 years), 210 non-dippers (Group 2) (mean age, 53.8 ± 15.8 years), 67 extreme dippers (Group 3) (mean age, 49.1 ± 15.9 years) and 102 dippers (Group 4) (mean age, 52.2 ± 12.5 years). Daytime mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) and night-time mean SBP and DBP were significantly different in groups (Group 1: 117 [90-193] mmHg and 71 [55-87] mmHg; Group 2: 137 [107-188] mmHg and 83 [107-188] mmHg; Group 3: 143 [115-193] mmHg and 88 [56-122] mmHg; and Group 4: 140.5 [116-173] mmHg and 76 [55-124] mmHg), p < 0.001; respectively. MPV and RDW levels were different in all four groups (p < 0.001). We found a significant difference in the rates of stroke and coronary artery disease between the four groups (p = 0.018 and p = 0.002, respectively). In the ROC curve analysis MPV had sensitivity of %77. 8 and specificity of 78. 1% for stroke when the cut-off value MPV was 9.25 (Area under curve: 0.808, 95% confidence interval: 0.726-0.889, p < 0.001). Conclusions: In our study, MPV and RDW levels and the rates of stroke and cardiovascular disease were significantly higher in non-dipper patients compared to other groups.